2022
DOI: 10.1007/s13721-022-00406-x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal networks in biology and medicine: a survey on models, algorithms, and tools

Abstract: The use of static graphs for modelling and analysis of biological and biomedical data plays a key role in biomedical research. However, many real-world scenarios present dynamic behaviours resulting in both node and edges modification as well as feature evolution. Consequently, ad-hoc models for capturing these evolutions along the time have been introduced, also referred to as dynamic, temporal, time-varying graphs. Here, we focus on temporal graphs, i.e., graphs whose evolution is represented by a sequence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…However, for a large network calculating betweenness centrality in a temporal graph is computationally very expensive. On the other hand researchers have found that finding the foremost and fastest walk is a P-hard problem [1,11,12].…”
Section: Issues In Implementing Centrality Measures For Temporal Graphsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for a large network calculating betweenness centrality in a temporal graph is computationally very expensive. On the other hand researchers have found that finding the foremost and fastest walk is a P-hard problem [1,11,12].…”
Section: Issues In Implementing Centrality Measures For Temporal Graphsmentioning
confidence: 99%
“…Static temporal graphs represent a snapshot of the graph at a specific time point, while dynamic temporal graphs represent the evolution of the graph over time. Temporal graphs can be represented as G(V, E, T ) where V is the set of vertices, T is the set of time stamp and E, a set of temporal edges, where each temporal edge is a triplet (u, v, t), with u, v ∈ V and t ∈ T [1]. Temporal graphs are particularly useful for modeling dynamic systems, such as social networks, transportation systems, and biological networks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, also the last task we consider, community search in temporal networks, finds applications in high-stake domains including medicine and epidemiology [66]. For instance, the algorithms we propose for community search in temporal networks may be valuable in guiding policy makers in the design of measures for preventing the spread of infectious diseases [28,65].…”
Section: Introductionmentioning
confidence: 99%